Qualitative Comparative Analysis (QCA), Anno 2013: Reframing The Comparative Method's Seminal Statements. Issue 2 (18th June 2013) - Rihoux, Benoît
Abstract This review article examines the ways in which QCA is being (re)framed by some main authors in the field, in a context of expansion and diversification of this approach and set of techniques. Charles Ragin's seminal The Comparative Method (1987) is first synthetized in the form of eight statements which are then confronted to eight recent book‐length publications: three QCA textbooks and five methodological volumes also touching upon QCA. On the whole, it appears that most statements have been considerably refined, both conceptually and technically, whereas only one statement is not taken on board anymore. In addition, QCA is being reframed and extended in different ways beyond Charles Ragin's initial statements.